The spread of Chinese virus in the internet discourse: a cognitive semantic analysis - Augustyn, Rafał; Prażmo, Ewelina (Penerbit Universiti Kebangsaan Malaysia, 2020)
In the present paper we examine the use of non-technical terms used to refer to the SARS-Cov2 virus, which – in a deliberate or non-deliberate fashion – stress the place of the virus’ origin. In particular, we consider the three following terms: Chinese virus, Wuhan virus, and Asian virus. Drawing on the cognitive semantics methodology, in particular, the notion of meaning potentials (Norén & Linell, 2007) and conceptual blending theory (Fauconnier & Turner, 2003; Brandt & Brandt, 2005; Oakley & Coulson, 2008) we aim to investigate the dynamics of meaning construal of the selected expressions in English-language Internet discourse. The main objective is to account for different interpretations of the same expressions as they are used in different contexts with, presumably, various intentions. Complex expressions such as compounds, tend to exhibit various meanings and thus, can be said to possess different meaning potentials which are activated differently depending on the contextual circumstances in the process of meaning construal, which – as we want to show in our analysis – is not always so intuitive. In this paper we thus argue that only a pragmatically-enriched model of dynamic meaning construal can account for the polysemy and frequent ambiguity of compound expressions, including semantic extensions with generally derogatory or even outright racist connotations.